Cognition in moral space: A minimal model - Beal, Bree; Gogia, Guram (Consciousness and cognition, 2021)
•Moral subjects and objects are defined by a subjective “morality threshold”.•Moral cognition is shaped by object perception in a few morally relevant dimensions.•Abstract moral values are epiphenomenal side-effects of this more basic process. We describe moral cognition as a process occurring in a distinctive cognitive space, wherein moral relationships are defined along several morally relevant dimensions. After identifying candidate dimensions, we show how moral judgments can emerge in this space directly from object perception, without any appeal to moral rules or abstract values. Our reductive “minimal model” (Batterman & Rice, 2014) elaborates Beal’s (2020) claim that moral cognition is determined, at the most basic level, by “ontological frames” defining subjects, objects, and the proper relation between them. We expand this claim into a set of formal hypotheses that predict moral judgments based on how objects are “framed” in the relevant dimensions of “moral space.”